Graphene Improves the Biocompatibility of Polyacrylamide Hydrogels: 3D Polymeric Scaffolds for Neuronal Growth - Martín, Cristina; Merino, Sonia; González-Domínguez, Jose M.; Rauti, Rossana; Ballerini, Laura; Prato, Maurizio; Vázquez, Ester (Scientific reports, 2017)
In tissue engineering strategies, the design of scaffolds based on nanostructures is a subject undergoing intense research: nanomaterials may affect the scaffolds properties, including their ability to interact with cells favouring cell growth and improving tissue performance. Hydrogels are synthetic materials widely used to obtain realistic tissue constructs, as they resemble living tissues. Here, different hydrogels with varying content of graphene, are synthesised by in situ radical polymerization of acrylamide in aqueous graphene dispersions. Hydrogels are characterised focusing on the contribution of the nanomaterial to the polymer network. Our results suggest that graphene is not a mere embedded nanomaterial within the hydrogels, rather it represents an intrinsic component of these networks, with a specific role in the emergence of these structures. Moreover, a hybrid hydrogel with a graphene concentration of only 0.2 mg mL −1 is used to support the growth of cultured brain cells and the development of synaptic activity, in view of exploiting these novel materials to engineer the neural interface of brain devices of the future. The main conclusion of this work is that graphene plays an important role in improving the biocompatibility of polyacrylamide hydrogels, allowing neuronal adhesion.